2012
DOI: 10.1111/j.1471-6712.2012.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

The patient satisfaction with nursing care quality: the psychometric study of the Serbian version of PSNCQ questionnaire

Abstract: The study provides a new tool for measuring patient satisfaction with nursing care in Serbia that may present a useful instrument for nursing care managers in improving the nursing care process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 31 publications
10
65
3
7
Order By: Relevance
“…This investigation show that there had been no significant differences in patients' fulfillment between age, sexual orientation, techniques for admission, in advance admission (2 years), and ward degree. The finding of this analysis has seemed to be inconsistence with earlier investigations which uncovered a significant relationship between patient fulfillment and age (Liu and Wang, 2007;Milutinović et al, 2012). In connection to sexual orientation, this investigation was not ready to close any distinction of patient fulfilment.…”
Section: Discussioncontrasting
confidence: 55%
“…This investigation show that there had been no significant differences in patients' fulfillment between age, sexual orientation, techniques for admission, in advance admission (2 years), and ward degree. The finding of this analysis has seemed to be inconsistence with earlier investigations which uncovered a significant relationship between patient fulfillment and age (Liu and Wang, 2007;Milutinović et al, 2012). In connection to sexual orientation, this investigation was not ready to close any distinction of patient fulfilment.…”
Section: Discussioncontrasting
confidence: 55%
“…The most frequent study design observed was instrument validation and only six cross-cultural adaptations were found 26,30,32,33,34,35 (Table 1). …”
Section: Methodological Qualitymentioning
confidence: 99%
“…Only three studies showed a unidimensional structure for the tested instrument 22,32,48 . However, there is not a clear pattern of what the essential dimensions (factors) that must be included in a satisfaction measurement are.…”
Section: Satisfaction Constructmentioning
confidence: 99%
“…Patient`s satisfaction is defined as patient's judgment on the goodness and quality of care [4]. Assessment of patient`s satisfaction with nursing care is very important to evaluate whether patient`s needs are fulfilled and thus facilitate planning and implementing appropriate nursing interventions for patient [5].…”
Section: Introductionmentioning
confidence: 99%